BIM Adoption for Facility Management in Urban Rail Transit: An Innovation Diffusion Theory Perspective. (9th December 2020) - Xu, Xiaodong; Wang, Guangbin; Cao, Dongping; Zhang, Zhujing
Abstract : Although building information modeling (BIM) has demonstrated to be an effective tool for the construction of urban rail transit worldwide, it has not gained the same popularity in the facility management (FM) of urban rail transit. The objective of this study is to investigate the BIM application areas for FM in urban rail transit from an innovation diffusion theory perspective, in order to gain efficient operation and maintenance (O&M) in urban rail transit. A total of 18 BIM application areas were first identified through semistructured interviews. A questionnaire survey was then conducted to further quantitatively characterize the relative advantage, ease of use, trialability, observability, and compatibility of these areas. Statistical analysis of the survey results provided evidence that, currently, BIM application areas directly related with facilities and equipment are most likely to be adopted. Correlation analysis further indicates that the perceived innovation diffusion characteristics of these BIM application areas significantly correlate with the development level of urban rail transit in different regions. The findings contribute to a broadened understanding of the complex innovation diffusion process of BIM for FM in urban rail transit and provide insights into how BIM can be more effectively adopted in the domain.